Biochemical responses of the marine mussel Mytilus galloprovincialis to petrochemical environmental contamination along the North-western coast of Portugal - Lima, Inês
Following the development of urban and industrial centres petrochemical products have become a widespread class of contaminants. The aim of this study was to investigate the effects of petrochemical contamination in wild populations of mussels (Mytilus galloprovincialis) along the NW Atlantic coast of Portugal by applying antioxidant and energetic metabolism parameters as biomarkers. For that, mussels were collected at five sampling sites presenting different petrochemical contamination levels. To evaluate the mussels' antioxidant status, enzymatic activities of catalase, superoxide dismutase, glutathione peroxidase, glutathione reductase, glutathione S-transferases, as well as glutathione redox status were evaluated in gills and digestive glands of mussels collected from the selected sites. Lipid peroxidation was determined in the same tissues to quantify cellular oxidative damage. Furthermore, to investigate how energetic processes may respond to these contaminants, the activity of NADP(+)-dependent isocitrate dehydrogenase was determined in mussels' digestive glands, and octopine dehydrogenase was determined in mussels' posterior adductor muscle. Furthermore, the concentrations of aliphatic hydrocarbons, unresolved complex mixture and polycyclic aromatic hydrocarbons (PAHs) were quantified in mussels' tissue, and abiotic parameters were quantified in water samples collected at each site. Several biomarkers showed statistically significant differences among sampling sites. The redundancy analysis (RDA) used to perform the integrated analysis of the data showed a clear separation of the sampling sites in three different assemblages, which are in agreement with the PAHs levels found in mussels tissues. In addition, the RDA indicated that some of the selected biomarkers may be influenced by abiotic parameters (e.g. salinity, pH, nitrates and ammonia). The approach selected for this study seems to be suitable for monitoring petrochemical contamination. (c) 2006 Elsevier Ltd. All rights reserved.